Rice-fish coculture: Enhancing resource management and food security - Samaddar, Ayan; Kacha, Dani; Kaviraj, Anilava; Freed, Sarah Johanna; Panemangalore, Arun Padiyar; Saha, Subrata (Elsevier, 2025)
Rice-fish coculture is an age-old nature-based practice that effectively utilizes land and water resources and promises to be a viable alternative to rice monoculture for sustainable joint production of rice and fish with socioeconomic and ecological advantages in rural areas. However, qualitative and quantitative studies on such practices to evaluate their socioeconomic vulnerability based on primary data of farmers' opinions are sparse. In this study, we attempted to identify the factors responsible for the success and lapses in rice-fish coculture in five villages of Ziro Valley in the lower Subansiri district of Arunachal Pradesh. We conducted an exhaustive field survey to collect primary data through questionnaires survey, focus group discussions, and interviews. Then, we analyzed the data by applying artificial intelligence and machine learning algorithms to identify the stresses and recommend guidelines to improve farmers' management and decision-making for sustainable rice-fish coculture. The results of the general linear regression, considering fifteen variables, Akaike information criterion, and the decision tree on three important responses of the farmers indicate that the the current practice of rice-fish coculture in the Ziro Valley yields poor returns. We identified that mismanagement of inputs, unwillingness to invest, nonavailability of adequate funds and formal training, and limited involvement of youths in the culture are crucial factors behind poor returns. However, institutional support in managing stocking density, feed, and rice type, along with human resource training, can address these gaps, thereby improving the production and livelihoods of a significant section of the Apatani tribe.